Sustainable Energy in Nigeria: An Integrated Women-Friendly Energy Supply Approach - C.N, Eze; C.C, Aduba; V.A, Arazu; K.T, Ughamba (International Journal of Sustainable Energy and Environmental Research, 2021)
Sustainable energy is at the center of pursuit of sustainable development goals (SDGs). Gender inequality, fueled by religious and cultural beliefs, has hampered the achievement of sustainable energy supply in Nigeria. Women, who are major consumers of energy, are largely excluded from energy production due to a relative deficiency in technical training. The paper focuses on integrating women in sustainable energy supply in Nigeria through the adoption of women-friendly energy production methods such as biogas production. The importance of installing household biogas plants in rural communities, providing relevant technical training for women, as well as cheap labor for servicing the biogas plants, and establishing accessible markets for sale of excess biogas were discussed. The economic potentials of well-packaged biogas feedstock, and bio-slurry (a by-product of biogas production) were highlighted to portray the win-win characteristics of biogas production.